Bahan Penderia untuk Pengesanan Aluminium Berasaskan Reagen Kolorimetrik Terdop dalam Filem Sol-Gel - Ahmad, Musa; Abdul Manaf, Norleen (Universiti Putra Malaysia Press, 2002)
Sol-gel technique was used in this study for sensing material preparation which could be used for aluminium detection in aqueous environment. Two organic reagents i.e. eriochrome cyanine R (ECR) and chrome azurol S (CAS), which are sensitive to aluminium were used in this study. The precursors used for the sol-gel solution preparation were tetraethyl orthosilicate (TEOS), water and ethanol in the volume ratio of 30:31:30. Dip-coating method was used to deposit the sol-gel solution onto microscope slide glass support to produce a thin sol-gel film. The study shows that the immobilised reagents have a good photo-stability, still maintaining their chemical properties as in free solution and regenerable by using NaF solution. The study also indicates that the reagen doped in sol-gel film still react with the analyze and could be potentially used as sensing material for aluminium detection.